Sustainability likelihood of Community and Social Development Project in Southwestern Nigeria - Eucharia Ejowokoghene Obar; Adegbenga Emmanuel Adekoya (Journal of Agricultural Extension, 2022)
This study investigated the gender and generational involvement of community members on the sustainability likelihood of the Community and Social Development Project (CSDP) in Oyo and Ekiti states, Nigeria. A multistage sampling procedure was used to select 130 respondents (16 youth, 42 adult male, 34 adult female and 38 elders). Focus group discussion was used to collect data. Thematic analysis was used to analyse the data. Respondents indicated their involvement in project phases: needs assessment (2:54, 6:5, 5:1), funding (2:23), decision making (12:4, 9:2, 7:2, 2:30), formulation of Community Development Plan (5:8, 3:3, 35:1), training (3:2, 6:6) and implementation (5:2, 2:25, 3:6, 9:3). None of the projects were insured (11:5, 2:26, 19:4), maintenance committee was set in place (8:32, 2:41), projects were relevant (19:7, 6:12, 20:10) and environmental impact assessment was carried out (7:8, 2:46, 3:13, 1:34). The facilitators of CSDP should monitor the activities of community members and ensure that the community members comply with the activities required for the implementation of the projects as stated in the CSDP implementation manual.